Analysis of Students' Higher Level Thinking Ability in Solving Mathematics Problems in View of Mathematical Logical Intelligence - Anastasia Maria Ikun; Stanislaus Amsikan; Ferdinandus Mone; Imanuel Faot (Pendidikan Matematika UNIMOR, 2023)
High-level Thinking Ability (HOT) is an ability or way of thinking that requires students to seek information or ideas in a certain way in remembering and restating or referring to something. HOT ability is influenced by several factors, one of which is logical intelligence, so the purpose of this study is to describe students' high-level thinking skills in solving mathematical problems in terms of Mathematical Logical Intelligence. This type of research is descriptive research with a qualitative approach. This research uses instruments in the form of test questions and interview guidelines to obtain students' ability to solve math problems. The research subjects are students of class VIIIC who have studied the material of System of Linear Equations of Two Variables (SPLDV). Based on the results of the analysis of student answers, the researcher describes that high ability students at the analysis stage are able to analyze incoming information and classify or formulate information into small parts to find out patterns and relationships, able to understand and distinguish the cause and effect of a complex scenario and identify or formulate questions. high ability students at the evaluation stage are able to provide an assessment of solutions, ideas and methods by using appropriate criteria or standards in determining the value of their effectiveness or benefits. High-performing students at the creation stage are able to draw conclusions about a particular idea or perspective, plan ways to solve problems, and rearrange elements or parts into a new structure that is different from the previous structure.